2017
DOI: 10.1017/cjn.2017.52
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Cerebral X-linked Adrenoleukodystrophy After Head Trauma

Abstract: A 21-year-old man with X-linked adrenoleukodystrophy (X-ALD) suffered a traumatic brain injury after a motor vehicle accident. He had been diagnosed with X-ALD after developing adrenal insufficiency ten years prior, but had no known neurologic involvement. Head magnetic resonance imaging (MRI) at the time of his motor vehicle accident revealed bilateral, frontalpredominant cerebral microbleeds, with no white matter abnormalities (Figure 1). After a 1-month hospital admission, he was transferred to rehabilitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…MRI observation of gadolinium enhancement in the brain remains the only method to detect this progression [ 17 21 ]. Infections or head trauma have been described as initiators of the conversion from AMN to ccALD, but typically no extrinsic factor can be identified [ 22 24 ]. Current treatment for ccALD includes hematopoietic cell transplant (HCT), but this must be performed at the earliest stages of the disease [ 12 , 14 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…MRI observation of gadolinium enhancement in the brain remains the only method to detect this progression [ 17 21 ]. Infections or head trauma have been described as initiators of the conversion from AMN to ccALD, but typically no extrinsic factor can be identified [ 22 24 ]. Current treatment for ccALD includes hematopoietic cell transplant (HCT), but this must be performed at the earliest stages of the disease [ 12 , 14 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also reported that the use of selective agonist of CB2r improved metabolic disturbances by rescuing GSK-3β-NRF2 axis and improved oxidative stress by induction of NRF2 antioxidant pathway [ 53 ]. Trauma or injury to the head triggers or activate symptoms in otherwise asymptomatic or arrested X-ALD patients [ 54 ]. It is possible that head trauma causes inflammatory response and thus followed by mitochondrial dysfunction, oxidative stress, and disruption of the BBB initiating the cerebral inflammatory demyelination and appearance of symptoms [ 55 ].…”
Section: Introductionmentioning
confidence: 99%